1997
DOI: 10.1116/1.580429
|View full text |Cite
|
Sign up to set email alerts
|

Properties of transparent conducting oxides formed from CdO and ZnO alloyed with SnO2 and In2O3

Abstract: In this article we examine the structural, electrical, and optical properties of several ternary alloy thin films. The alloys are zinc oxide and cadmium oxide, each of which was reacted with both indium oxide and tin oxide to form sputtering targets. The films were deposited by rf sputtering. X-ray diffraction spectroscopy showed that cadmium stannate, cadmium indate, and zinc stannate films were all polycrystalline spinel phase, but only when deposited at room temperature in pure oxygen and then annealed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(72 citation statements)
references
References 0 publications
10
61
1
Order By: Relevance
“…Figure 3 shows the optical transmittance spectra of undoped and Mg-doped Sn 2 S 3 thin films recorded in the wavelength range of 300-1100 nm. The average transmittance of the Mg-doped Sn 2 S 3 films decreases with increase in the Mg content which may be due to increased absorption by free carriers [18]. It is also observed that the absorption edge of the doped films shift towards lower wavelength side which indirectly indicate an increment in their band gap values.…”
Section: Electrical Studiesmentioning
confidence: 65%
“…Figure 3 shows the optical transmittance spectra of undoped and Mg-doped Sn 2 S 3 thin films recorded in the wavelength range of 300-1100 nm. The average transmittance of the Mg-doped Sn 2 S 3 films decreases with increase in the Mg content which may be due to increased absorption by free carriers [18]. It is also observed that the absorption edge of the doped films shift towards lower wavelength side which indirectly indicate an increment in their band gap values.…”
Section: Electrical Studiesmentioning
confidence: 65%
“…Table 2 shows the electrical properties of the pulsed arc-grown ICO films compared to values reported for several other growth techniques. Except for the optimized PLD-grown films [19], the electrical properties of films prepared by PFCAD in this study are typically better than those of ICO films prepared by other techniques on glass or even on single crystalline MgO substrates [10,12,14,30,[33][34][35][36]. Though the as-deposited films in this study show a little higher resistivity than that of the optimized PLD-grown films, comparable mobility with a higher near infrared transmittance and a much wider transparent range are observed, which is of special interest to multi-junction solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…CdIn 2 O 4 has a wide optical energy gap and has been studied because of its high electrical conductivity and transparency in the visible light region. CdIn 2 O 4 materials are applied in gas sensors and devices such as solar cells, flat panel displays, invisible security circuits, and windshield defrosters [1][2][3][4][5]. The energy gap, crystal structure, and photoluminescence (PL) of pure CdIn 2 O 4 have been studied [4][5][6], but no research has been conducted on pure CdIn 2 O 4 doped with 4f species.…”
Section: Introductionmentioning
confidence: 99%
“…CdIn 2 O 4 materials are applied in gas sensors and devices such as solar cells, flat panel displays, invisible security circuits, and windshield defrosters [1][2][3][4][5]. The energy gap, crystal structure, and photoluminescence (PL) of pure CdIn 2 O 4 have been studied [4][5][6], but no research has been conducted on pure CdIn 2 O 4 doped with 4f species. As a method of changing the electrical resistance of compound semiconductors and to widen the light energy region with photoelectric sensitivity, the effects of doping with 4f materials on the electrochemical characteristics should be evaluated.…”
Section: Introductionmentioning
confidence: 99%